Abatacept and granulocyte-colony stimulating factor in a patient with rheumatoid arthritis and neutropenia. (October 2017) - Priora, Marta; Parisi, Simone; Scarati, Marco; Borrelli, Richard; Peroni, Clara Lisa; Fusaro, Enrico
Neutropenia in patients with inflammatory diseases increases the risk of infection due to the disease itself and the related immunosuppressive treatments. We report the case of a 54-year-old female with rheumatoid arthritis and following development of chronic neutropenia. All investigations excluded pathogenic relations with drugs and/or other clinical situations; the gravity of neutropenia required a treatment with G-CSF and the increased articular inflammatory activity justified a biologic-therapy, abatacept (CTLA4 inhibitors). The juxtaposition of immunostimulants and immunosuppressors led to great effectiveness for both hematological and rheumatic issues. To date, while some biologic drugs (TNF, IL6R and CD20 inhibitors) have reported relations with neutropenia,  no such relevance subsists for Abatacept. Our case reports the experience of the safe effective use of abatacept and G-CSF for 8 years.